2020
DOI: 10.3390/app10051849
|View full text |Cite
|
Sign up to set email alerts
|

Deadbeat Predictive Current Control for Circulating Currents Reduction in a Modular Multilevel Converter Based Rail Power Conditioner

Abstract: This paper presents a deadbeat predictive current control methodology to reduce the circulating currents in a modular multilevel converter (MMC) when it operates as a rail power conditioner (RPC) in a conventional railway system-based V/V connection. For this purpose, a half-bridge MMC based on half-bridge submodules, operating as an RPC is explained, and the total system is denominated as a simplified rail power conditioner (SRPC). The SRPC in this study is used to compensate harmonics, reactive power, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…The biggest implementation challenges based on this topology lies essentially in balancing the DC-link voltage of each submodule. In this context, deadbeat predictive current control methodology to reduce the circulating currents and balancing the submodule voltages in the MMC is presented in [11]. Moreover, each submodule will contribute to a portion of the total power, which causes currents circulating in the submodules.…”
Section: Half-bridge Submodulementioning
confidence: 99%
“…The biggest implementation challenges based on this topology lies essentially in balancing the DC-link voltage of each submodule. In this context, deadbeat predictive current control methodology to reduce the circulating currents and balancing the submodule voltages in the MMC is presented in [11]. Moreover, each submodule will contribute to a portion of the total power, which causes currents circulating in the submodules.…”
Section: Half-bridge Submodulementioning
confidence: 99%
“…Nowadays, the majority of the commercial MMC projects are based on the indirect AC/DC/AC MMC with half-bridge SMs [54]. This is due to the high efficiency of the half-bridge SM, besides its lower cost and simpler construction comparing to other types of SM [55].…”
Section: Rpc Based On a Full-bridge Indirect Modular Multilevel Convementioning
confidence: 99%
“…Each half-bridge SM contains two switching devices and one capacitor that can be inserted or bypassed. The arm inductors are important to adjust the circulating current value between the MMC legs (the circulating currents are produced due to the inner DC-voltage differences between the MMC SMs [55]). In this topology, ITs with a turns ratio 1:1 are necessary to interface between the converter and the traction power grid.…”
Section: Rpc Based On a Full-bridge Indirect Modular Multilevel Convementioning
confidence: 99%
“…For a small sampling period, Ts, it can be considered that the variation of ierror, is almost constant. Additionally, it can be concluded that the effectiveness of this control technique is directly influenced by the quality of the considered system model [31].…”
Section: Current Control Algorithmmentioning
confidence: 99%
“…Additionally, it can be concluded that the effectiveness of this control technique is directly influenced by the quality of the considered system model [31]. By analyzing Figure 7, it is possible to perceive the existence of two input control algorithm blocks: MPPT Control and BESS Control.…”
Section: Current Control Algorithmmentioning
confidence: 99%